(3BKGQ GdHdGOs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s ((3MSjf Hf YKeGf Hf MSjf GdMGaX GdeYde s)
(3ChdgG (B:s
(3jbhd GdYHO HYO MeO Gddg MeOkG jQVjg Efi bO LeYJ ai gPG GdcJGH eG hbY di hYQaJg hSeYJ Hg hTGgOJg ai HdGOg hYHGOg s
(3BNQgG (B:s
(3hbO Ndb Gddg JYGdi ai hSWgG LdOkG UajbkG cGdKhH ef SQJgG Edi QcHJgG djSJQ YhQJgG aHbjJ YfOge eOI GfJgi Yde Cgd HdGOfG hGddg CYde s
(3HChdg agQSJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B183s
Keywords: (3GdLZQGajG h GdHdOGfs